Speech to Braille Convertor for Visually Impaired Using Python - Swathi Subhash, Shreya Guru, Payal. P. Jain, Sushma., Dr. Ravi Kumar M.G (International Journal of Advanced Science and Technology, 2020)
In the current times the report shows that around 285 million of the world’s population are visually impaired and 39 million are blind and over 12 million are from India which makes India home to one third of world’s blind population. This includes mild to severe cases. They use the Braille language to read any type of data with their sense of touch but many issues are being faced in accessing the text which is not in Braille script. Here we are proposing a prototype which converts speech into Braille script. In this work, the speech is taken as input which is converted into text and later with the help of python packages used it will be converted into Braille script without any hassle. This would help many people to easily convert any material into Braille script just by using their voice. With the help of this the differently abled can lead just as accustomed life as an abled person.